To simplify the polynomial \((b+8)(3b-6)\), we will use the distributive property (also known as the FOIL method for binomials):
\[ (b+8)(3b-6) = b \cdot 3b + b \cdot (-6) + 8 \cdot 3b + 8 \cdot (-6) \]
Now, let's calculate each term:
- \(b \cdot 3b = 3b^2\)
- \(b \cdot (-6) = -6b\)
- \(8 \cdot 3b = 24b\)
- \(8 \cdot (-6) = -48\)
Now, we combine these results:
\[ 3b^2 - 6b + 24b - 48 \]
Next, we combine the like terms \(-6b\) and \(24b\):
\[ 3b^2 + (24b - 6b) - 48 = 3b^2 + 18b - 48 \]
So, the simplified polynomial is:
\[ \boxed{3b^2 + 18b - 48} \]